THE ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN READING COMPREHENSION: A CASE STUDY AT SMP NEGERI 3 KOMBI - Tamuntuan, Zefanya Patricia; Tuerah, Ignatius J. C.; Pabur, Herminus Efrando (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
Reading is one of the most used activities in English Language Learning (ELL), however many students struggle with reading skill in English classroom. The present study aims at investigating the learning difficulties faced by students in reading text and the factors contributing to the learning difficulties. The study conducted at SMP Negeri 3 Kombi employs qualitative method with case study design. Eight 9th-grade students are chosen as the sample of the study using purposive sampling. Data collected from documentation and interview are analyzed through the 3 steps of qualitative data analysis namely data condensation, data display and drawing and verifying conclusion. The findings showed that 9th grade students at SMP Negeri 3 Kombi faced learning difficulties in reading recount text. The learning difficulties they faced are vocabulary (55%), making inference (45%), determining main idea and finding detailed information (35%). Factors such as limited vocabulary, fluency, familiarity with the subject matter and ineffective reading strategies contribute significantly to students reading difficulties. Other factors such as weak verbal reasoning, level of difficulty, and information retention also contribute to the reading difficulties faced by the students. This study suggests that teachers need to use various strategies to tackle the reading difficulties faced by the students.